O PAPEL DO CONHECIMENTO NA FORMAÇÃO DA EXPECTATIVA DE UMA EQUIPE DE DESENVOLVIMENTO DE SOFTWARE: UM ESTUDO DE CASO NA TIC DA PETROBRAS - Oest, Carlos Henrique Magalhães (2012)
This paper examines the importance of knowledge in the formation of the vision of a team within a software development project. Therefore we conducted a literature review establishing the relationships between efficiency, knowledge, and vision training in organizations, resulting in the realization that in order for a group of people to form an effective team is needed the availability of material resources, which individual views are converging on the critical factors that determine the success of the action, besides different backgrounds and experiences - knowledge and experience - they can lead to divergent views, hindering the effectiveness of collective action. In this sense, the literature review which established the Critical Success Factors related to the specific type of software development project adopted as the research object support. The field research was conducted with a team of software development by Petrobras, using a questionnaire. In the research were involved people performing different roles on the team, seeking the views and experiences of each knowledge regarding the Critical Success Factors of the project. Data analysis involved the application of quantitative techniques for analyzing relationships between a set of explanatory variables (position on the team and sources and Degree of Knowledge) and a set of variables to explain (vision of the project context and vision of expectations success of the project). We saw that staff researched strongly shares the organizational vision, built with base on the literature for the context of the project, and found significant evidence of the important role of "Tacit Knowledge" in the formation of the vision of the project context (perception of Critical Success Factors relevant to the project). The "Degree of Knowledge" is also associated with greater sharing of vision. However, we have not found a direct relationship between knowledge and expectation that each individual team forms on the success of the project, which may indicate how the project is innovative resources and context visible to the respondents do not agree with the shared vision built with base on the literature existent.